Hong Kong: Warrants Aim at Activists Abroad - Human Rights Watch (Human Rights Watch, 2023)
Hong Kong authorities have issued baseless arrest warrants and HK$1 million (US$128,000) bounties on eight exiled democracy activists and former legislators that expand China’s political intimidation campaign beyond its borders.
Keywords: 2023-07 July; Hongkong